The influence of knowledge and attitude of female adolescents on Fe tablet consumption at Public Senior High School 1 of Gorontalo City, Indonesia - Zuriati Muhammad; Sri Sumarmi (AOSIS, 2019)
Female undergo menstruation, pregnancy and breastfeeding, which bring about the need to consume blood cell tablet in order to provide extra iron and further replace lost blood, as a preparation through adolescence. Furthermore, females tend to suffer from anemia, exhibit retarded learning, working competence, quality of human resources and overall wellbeing of their offspring hence the promotion of nutritional status and health is essential (Warsiti, 2013). This study therefore aims to investigate the effect of knowledge and attitudes of female adolescents on the consumption of Fe tablet at Public Senior High School 1 of Gorontalo, applying a quantitative approach with cross-sectional method. With a sample of 72 students, the study involved the use of a questionnaire to obtain data, which were analyzed using the Fisher Ex cact (X2) test at the significance level of 95% (α=0.05). The analysis results revealed no influence of knowledge, toward the behavior of consuming Fe tablet with p-value = 0.355. Furthermore, there was a correlation between attitudes and consumption behavior, with p-value = 0.003 among young women in Public Senior High School.